Hal-Hal Yang Ada Hubunganya Dengan Terjadinya Preeklampsia Pada Ibu Hamil Yang Berobat Jalan Dan Di Rawat Inap Di Poliklinik Kebidanan Dan Penyakit Kandungan RSUD Labuang Baji Makassar - Intang, Ambo Upe; Amiruddin, Tedy; Murnita, Ika Azdah (Fakultas Kedokteran Universitas Bosowa, 2025)
Preeclampsia is a specific pregnancy syndrome that occurs after 20 weeks of gestation in previously normotensive women. It is characterized by high blood pressure (>140/90 mmHg) accompanied by proteinuria. Proteinuria >0.3 g/24 hours or +1 on qualitative examination, along with the onset of hypertension after 20 weeks of gestation in previously normotensive women1. There are several risk factors associated with the development of preeclampsia in pregnant women. These risk factors can be divided into modifiable and non-modifiable factors. The aim of this study was to determine the factors associated with preeclampsia in patients receiving outpatient and inpatient care at the Obstetrics and Gynecology Polyclinic of Labuang Baji Regional General Hospital in Makassar based on (1) classification, (2) age, (3) parity, (4) history of preeclampsia, (5) chronic hypertension, and (6) multiple pregnancies. This study was conducted on 80 patients receiving outpatient and inpatient care at the Obstetrics and Gynecology Polyclinic of Labuang Baji Regional General Hospital in Makassar from 2020 to 2021. The study utilized an observational analytical method with a case-control study design using secondary data from medical records of preeclampsia patients receiving outpatient and inpatient care at the Obstetrics and Gynecology Polyclinic of Labuang Baji Regional General Hospital in Makassar. The data analysis was performed using SPSS software. The results of this study showed the distribution of preeclampsia patients receiving outpatient and inpatient care at the Obstetrics and Gynecology Polyclinic of Labuang Baji Regional General Hospital in Makassar: (1) The majority of preeclampsia cases were classified based on age (65.0%), (2) The majority of cases occurred in the high-risk parity group (75.6%), (3) There were more cases with a history of previous preeclampsia at risk (70%) compared to cases without risk (42.5%), (4) There were more cases with high-risk chronic hypertension (95.2%) compared to cases with non-risk chronic hypertension (13.2%), (5) There were more cases with non-risk multiple pregnancies (57.4%) compared to cases with high-risk multiple pregnancies (52.6%). In conclusion, preeclampsia patients were most prevalent in the age group <20 and >35, parity, history of preeclampsia, chronic hypertension, and non-risk multiple pregnancies.